Orthognathic surgery in class 3 malocclusion patients and implant treatment in edentulism patients.. - B Asher, Pranav; Lone, Faizan ali; Parameshwaran, V. N.; R Varshney, Shruti; Gupta, Kanishk; Husai, ishrat (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to assess orthognathic surgery in class 3 malocclusion patients and implant treatment in edentulism patients. Material and methods: This study comprised of 100 individuals. All the subjects had been explained about the study procedure and were asked to give consent. The participants underwent oral clinical examination. It was found that 50 subjects had class 3 malocclusion and 50 subjects had edentulism. The subjects were divided into two groups. Group 1 comprised of subjects with class 3 malocclusion and group 2 comprised of subjects with edentulism. The treatment plan was prepared for these individuals and the findings were compared and tabulated. Statistical analysis was conducted using SPSS software. Results: In this study, there were 50 subjects in group 1 (class 3 malocclusion) and there were 50 subjects in group 2 (edentulism). There were total 45 males and 55 females in this study with 26 males and 24 females in group 1 and 19 males and 31 females in group 2. All the subjects with class 3 malocclusion underwent orthognathic surgery for treatment and all the subjects with edentulism underwent dental implant treatment. Conclusion: From the findings of the study, it can be concluded that there was equal prevalence of class 3 malocclusion and edentulism in this study. Females were more effected as compared to men. All the subjects with class 3 malocclusion underwent orthognathic surgery and dental implant treatment was planned for the subjects with edentulism